PENYESUAIAN DIRI DAN STRES AKADEMIK MAHASISWA TAHUN PERTAMA - Ferina Ulfa Nikmatun Erindana; H Fuad Nashori; Muhammad Novvaliant Filsuf Tasaufi (MOTIVA: JURNAL PSIKOLOGI, 2021)
The purpose of the research to know the corelation between self adjustment and academic stress in first-year university students faculty psychology and cultural social science of Indonesian Islamic University. Researchers conducted data retrival using the academic stress scale and self adjustment scale.  Respondents in this research were 170 first-year university students. From the result of a test of corellation it was found there is a significance correlation between self adjustment and academic stres (p<0,05) with value of siginificance p=0,000. The coeffficient correlation (r) of the test hypothesis is -0,569, which indicate a negative relationship between of theese two variabels. This means that if first year university students can adjust to the college environment it will reduce the perceived academic stress. Conversely, if first year university students s are less able to adjust to to the college environment, it will increase the academic pressure felt by first year students.Keywords: Academic stress, Self Adjustment, first-year university students